Reconstructive procedures in maxillofacial oncosurgery - Pink, Richard; Molitor, Martin; Tvrdy, Peter; Michl, Petr; Pazdera, Jindrich; Zboril, Vitezslav; Zalesak, Bohumil (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2016)
OBJECTIVE: Oropharyngeal cancers are a biologically heterogenous group of tumors with diverse risk factors including tobacco, alcohol, HPV, inherited disorders, the acquired immunodeficiency of Karposi's Sarcoma and non Hodgkin's lymphoma. In the Czech Republic, oropharyngeal cancers represent around 2% of all cancers. The treatment of these tumors is long and complex. Reconstructive procedures in maxillofacial oncosurgery demand good interdisciplinary collaboration and great professional preparedness of the surgical and nursing team. Patient age and stage of disease, including the presence of metastases are of key importance. A prerequisite for the success of surgical treatment is removal of the tumor with a sufficient safety margin. Reconstructive procedures then follow. AIM: To highlight the importance of radical tumor resection and describe reconstruction of the defect in a group of our patients. METHODS AND RESULTS: From 2008 to 2013, 23 patients with oropharyngeal carcinoma underwent radical surgical removal of tumor, followed by reconstruction of postoperative defects using distant and free flaps. The histopathology showed predominantly squamous cell carcinomas and one of Merkel cell carcinoma. 16 patients had malignant disease detected in III-IV. In only 7 cases was treatment initiated in the first and second stages of the disease. In these patients, the tumors were removed with a safety margin of healthy tissue and in none, did the basic cancer recur . The postoperative course in terms of flap engraftment and overall condition of the patient was uneventful. All of these patients still enjoy a good life quality with a current mean survival in range 5 - 76 months. Radical surgical removal of a malignant tumor in the early stages of the disease is associated with fewer postoperative complications and longer survival. CONCLUSION: To avoid the risk of local and/or systemic postoperative complications, appropriate patient selection is important. Overall, the traditional, classic reconstructive procedures with the use of prostheses, in many cases is still the best option in our experience.
Keywords: reconstruction of defects; nádory kůže; Humans; Skin Neoplasms; Carcinoma, Merkel Cell; Female; Oropharyngeal Neoplasms; výsledek terapie; lidé; reoperace; Surgical Flaps; free flaps; nádory orofaryngu; stomatochirurgické výkony; ženské pohlaví; Male; Treatment Outcome; Merkelův nádor; chirurgické laloky; spinocelulární karcinom; Carcinoma, Squamous Cell; mužské pohlaví; Oral Surgical Procedures; Reoperation